Effect of nano-SiO2 and nano-CaCO3 on the static and dynamic properties of concrete - Wang, Zhi-hang; Bai, Er-lei; Xu, Jin-yu; Du, Yu-hang; Zhu, Jing-sai (Scientific reports, 2022)
Three kinds of nano-concrete, i.e., 2.0% nano-SiO 2 doped, 2.0% nano-CaCO 3 doped and 1.0% nano-SiO 2 -1.0% nano-CaCO 3 co-doped concretes (NS, NC, NSC) were prepared for a study on static property and dynamic property under different strain rates (50–130 s −1 ) using HYY series hydraulic servo test system and Φ100 mm split Hopkinson pressure bar test system, and a comparison with plain concrete (PC) as well. The results have shown that under static load, as compared with PC, NC has both strength and elastic modulus increased obviously, while NS has strength decreased and elastic modulus increased, and under dynamic load, there is an obvious strain rate effect for the dynamic compressive strength, impact toughness, energy dissipation and impact failure mode of concrete. Under the same strain rate, the dynamic compressive strength, peak strain, impact toughness and energy dissipation of NC are significantly increased, while its dynamic elastic modulus is decreased. Compared with PC, NS has dynamic compressive strength, peak strain, impact toughness and energy dissipation decreased, and dynamic elastic modulus increased, NC has static and dynamic mechanical properties improved, NS has static and dynamic mechanical properties weakened, and NSC is between PC and NC in static and dynamic mechanical properties, but generally improved. Doped with nano-CaCO 3 , NC has compactness improved, weak areas reduced, and pore size distribution optimized, while doped with nano-SiO 2 , NS has obvious internal weak areas, with pore structure degraded.